THE RESILIENCE OF URBAN REFUGEES THROUGH A LIVELIHOOD PROGRAM AT THE JESUIT REFUGEE SERVICE - Fadilah, Bazlin; Fuaida, Lisma Dyawati (Social Welfare Study Program, 2022)
Abstract. Asian countries have often been the targets of the mobilization of refugees who migrate to seek protection, including Indonesia. Most refugees live independently in populated areas and alongside local urban residents in the country. These urban refugees who come to Indonesia experience serious difficulties, especially from the limited work opportunity that affects their resilience. Their existence encourages a non-profit community organization, Jesuit Refugee Service (JRS), located in Bogor, Indonesia, with its livelihood program to help refugees support their life survival. This study aims to explore and understand how a livelihood program supports the resiliency of urban refugees. The subjects in this study were four urban refugees who lived independently and participated in the livelihood program. The research is descriptive qualitative research. Data collection techniques in this study consist of interviews, observation, and documentation studies. The research results conclude that the four urban refugees have better resilience obtained from the support and benefits of the livelihood program. The four urban refugees have resilient individual traits ranging from social competence, autonomy, problem-solving skills, and awareness of goals and the future that are obtained through the stages of resilience (succumbing, surviving, recovering, thriving) and the supporting factors of resilience (I Am, I Have, and I Can). Keywords: Resilience; Urban Refugees; Livelihood Program. Abstrak. Negara-negara Asia sering menjadi sasaran mobilisasi para pengungsi yang bermigrasi untuk mencari perlindungan, termasuk Indonesia. Sebagian besar pengungsi tinggal secara mandiri di daerah berpenduduk dan bersama penduduk perkotaan lokal di negara ini. Pengungsi perkotaan yang datang ke Indonesia ini mengalami kesulitan yang serius, terutama dari terbatasnya kesempatan kerja yang mempengaruhi ketahanan mereka. Keberadaan mereka mendorong sebuah organisasi masyarakat nirlaba, Jesuit Refugee Service (JRS), yang berlokasi di Bogor, Indonesia, dengan program mata pencaharian untuk membantu para pengungsi mendukung kelangsungan hidup mereka. Penelitian ini bertujuan untuk menggali dan memahami bagaimana program mata pencaharian mendukung ketahanan pengungsi perkotaan. Subjek dalam penelitian ini adalah empat pengungsi perkotaan yang hidup mandiri dan mengikuti program mata pencaharian. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini terdiri dari wawancara, observasi, dan studi dokumentasi. Hasil penelitian menyimpulkan bahwa keempat pengungsi perkotaan memiliki ketahanan yang lebih baik yang diperoleh dari dukungan dan manfaat dari program mata pencaharian. Keempat pengungsi perkotaan memiliki ciri-ciri individu resilien mulai dari kompetensi sosial, otonomi, keterampilan memecahkan masalah, dan kesadaran akan tujuan dan masa depan yang diperoleh melalui tahapan resiliensi (succumbing, survival, recovery, thriving) dan faktor pendukung resiliensi. (Saya Ada, Saya Punya, dan Saya Bisa). Kata kunci: Resiliensi; Urban Refugees; Program Livelihood.